2016
DOI: 10.1039/c6cc02522f
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Rh-catalysis: decarboxylative β-keto acid and alkyne cross-coupling

Abstract: Herein, we describe a regioselective Rh-catalyzed decarboxylative cross-coupling of β–keto acids and alkynes to access branched γ,δ–unsaturated ketones. Rh-hydride catalysis enables the isomerization of an alkyne to generate a metal-allyl species that can undergo carbon-carbon bond formation. Ketones are generated under mild conditions, without the need for base or activated electrophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(19 citation statements)
references
References 77 publications
0
18
0
1
Order By: Relevance
“…In 2016 the Dong group reported an alternative approach to the synthesis of ,-unsaturated ketones from internal alkynes using a -keto acid as the nucleophile by tandem Rh catalysis (Scheme 54). 74 They studied the relationship between ligand bite angle and reactivity and found that the optimal bite angle of approximately 101° (DPEphos, L15) promotes the desired transformation efficiently.…”
Section: Scheme 53 Rh-catalyzed Addition Of 13-dicarbonyl Compounds mentioning
confidence: 99%
“…In 2016 the Dong group reported an alternative approach to the synthesis of ,-unsaturated ketones from internal alkynes using a -keto acid as the nucleophile by tandem Rh catalysis (Scheme 54). 74 They studied the relationship between ligand bite angle and reactivity and found that the optimal bite angle of approximately 101° (DPEphos, L15) promotes the desired transformation efficiently.…”
Section: Scheme 53 Rh-catalyzed Addition Of 13-dicarbonyl Compounds mentioning
confidence: 99%
“…Related reactions of internal alkynes were subsequently developed and applied to the synthesis of heterocycles (Scheme ) . In 2016, the groups of Dong and Breit simultaneously demonstrated that direct access to γ,δ‐unsaturated ketones may be achieved in decarboxylative coupling reactions of alkynes with β‐keto acids (Scheme ) ,…”
Section: Alkynes As Electrophilic π‐Allyl Precursorsmentioning
confidence: 99%
“…However, since the first catalytic example was reported by Evans, different catalytic systems and electrophilic substrates have been developed to overcome the intrinsic instability of β ‐ketoacids . Among all methods explored so far, the Lewis acid catalysed decarboxylative additions of β ‐ketoacids are rare, only several reports about have been demonstrated with narrow scopes ,,,. Therefore, it is still highly desirable to develop reactions involving Lewis‐acid catalysed decarboxylative addition of β ‐ketoacids to new acceptors.…”
Section: Methodsmentioning
confidence: 99%